Drafting eligible biotech and immunotherapy claims - Shyh-Jen Wang (Taylor & Francis Group, 2019)
The very recent US Supreme Court and Court of Appeals for Federal Circuit (CAFC) cases have dramatically changed the standard of patent eligibility. Several groundbreaking innovations were thus determined to be patent ineligible. The patent ineligibility would impact on the innovation s of the field of biomarkers, diagnostic methods and personalize cancer immunotherapy. To solve the thorny problem of eligibility, this study retrospectively analyzes all CAFC related cases and presents a flow chart determining patent eligibility based on the courts' decisions. Our analysis indicates the best way to avoid eligible rejection or invalidation is that an invention cannot fall within the categories of natural law, natural phenomenon or abstract idea. Thus, claiming non-natural cDNA, involving a step to grow a transformed cell or adding a means clause in a method claim would be some possible solutions. Moreover, based on the flow chart, even though a claim with substantive limitation but not well-understood, routine or conventional activities would be patent eligible; no one has successfully made the argument in the CAFC so far. We believe that this flow chart can serve as a set of guidelines for determining patent eligibility.